Islamic Agility Investment (IAI) Approach in Financial Inclusion: Islamic Agility Investment (IAI) Approach in Financial Inclusion - Yuyun Ristianawati Yuyun; Setyo Budi Hartono (International Journal of Seocology, 2023)
The concept of Islamic Agility Investment (IAI) is a development of strategic agility diversification investment (SADI) in the area of benevolent funds for Islamic financial institutions. The aim is to open up financial inclusion in financing contracts such as mudharabah and musyarakah. SADI is derived from the two basic theories of RBT and portfolios which through the Qur'anic approach receive treatment in the form of morality, kindness, and empathy. While the methodology used is to mix the derivations of each of these basic theories in producing a slick IAI proposition. As a result, IAI becomes a tool in non-financial measurement that is used to assess the morals, trust, and seriousness of customers in obtaining soft working capital in benevolent funds.